ALDH1 is a prognostic factor for patients treated with neoadjuvant chemoradiotherapy and radical resection for stage III rectal cancer. Issue 2 (30th September 2014) - Oh, Seung Yeop; Sohn, Se Hwa; Yim, Hyunee; Lee, Dakeun; Suh, Kwang Wook; Kim, Young Bae
<x xml:space="preserve">Abstract</x> Background and Objectives The factors relating to changes within a tumor after preoperative chemoradiotherapy associated with rectal cancer prognosis remain to be determined. The aim of this study was to investigate the expression of CD133 and ALDH1 and to analyze the predictive and prognostic roles in patients with rectal cancer after chemoradiotherapy. Methods We analyzed the expression levels of ALDH1 and CD133 in patients with middle and lower rectal cancers who underwent preoperative chemoradiotherapy between March 2005 and December 2011. Results The expression of CD133 was not associated with survival. The 5‐year overall survival rates were lower in patients with high ALDH1 expression compared to low ALDH1 expression in stage III rectal cancer (61.0% vs. 89.7%, P = 0.031). Cox multivariate analysis demonstrated that high ALDH1 expression (HR, 5.425; 95% CI, 1.116–26.373; P = 0.036), cT (HR, 12.861; 95% CI, 2.188–75.591; P = 0.005), and pN2 (HR, 28.481; 95% CI, 4.757–170.518; P < 0.001) were independently associated with overall survival in 51 patients with stage III rectal cancer. Conclusions Expression of ALDH1 indicates a more aggressive feature of stage III rectal cancer and can stratify stage III rectal cancer into different survival groups. J. Surg. Oncol. 2015 111:243–247. © 2014 Wiley Periodicals, Inc.